Cannibalistic behaviour of the first and second instar larvae of Plodia interpunctella (Hübner), Cadra cautella (Walker), Ephestia kuehniella Zeller, Corcyra cephalonica (Stainton) (Lepidoptera Pyralidae) under starvation (Bollettino di zoologia agraria e bachicoltura, 2024)
Tests were carried out at three different environmental conditions: 18°C and 65% RH; 24°C and 63% RH; 28°C and 70% RH. Results can be summarised in the following: cannibalism was confirmed for P. interpunctella, C. cautella, E. kuehniella, C. cephalonica; it is more frequent at 28°C than 24 °C and l8°C; the probability of cannibalism depends on larval instar; cannibalism is more frequent in presence of different larval stages; the choice of the victim is made towards more vulnerable individuals, that are less resistant to the attack (no first instar larva was able to cannibalise a second instar one); at 28°C the survival time of cannibal first and second instar larvae is, with some exceptions, greater than those of starved larvae of the same stage.
Keywords: cannibalism; larval behaviour; larval survival; moths of stored products